Schools for special needs, 2010-2011 : a fully comprehensive guide to special needs education in the United Kingdom (London : Kogan Page Ltd, 2010)
'Schools for Special Needs' provides a comprehensive directory of special schools and colleges throughout the UK. It gives details of the care and special facilities that these schools provide and features a number of full- and half-page profiles